Distributed seasonal and annual mass balance measurements of Wolverine Glacier, Alaska, using geodetic surveys and emergence velocities - Zeller, Lucas R., author; McGrath, Daniel, advisor; Aster, Richard C., committee member; Leisz, Stephen J., committee member (Colorado State University. Libraries, 2021)
Glaciers are key components of human-environmental systems worldwide. They are a source of fresh water for human consumption, crop irrigation, and hydroelectric power even during times of drought. Glaciers promote environmental and ecological heterogeneity by modulating stream temperatures and providing key nutrient, geochemical, and sediment fluxes, are popular tourism destinations, and introduce risks from natural hazards such as glacier-lake outburst floods. Glaciers have undergone dramatic retreat and thinning over the past 50 years, and these trends are predicted to accelerate through the 21st century. Short term (seasonal to annual) measurements of glacier mass balance provide valuable insight on how glaciers respond to climatological forcings and the processes that drive those changes. However, in-situ measurements are prohibitively time consuming, logistically difficult, and prone to uncertainty, rendering them insufficient for global-scale analyses. The increasing availability of high-resolution geodetic products offers promising opportunities for measuring mass balance from a remote platform if the confounding effects of ice emergence velocities and firn compaction on surface elevation can be correctly constrained. In this study, I present spatially and temporally distributed measurements of emergence velocities on Wolverine Glacier, Alaska, derived from three methods: 1) repeat Global Navigation Satellite System (GNSS) measurements of mass balance stakes, 2) modelled from annual mass balance measurements and glacier thinning rates, and 3) a novel approach of differencing geodetic surveys and snow depths derived from ground penetrating radar surveys. These emergence velocities, in conjunction with estimates of firn compaction, were used to measure distributed mass balances of Wolverine Glacier over three winter seasons, one summer season, and two annual time periods via geodetic surveys. The three approaches to measuring emergence velocity showed overall agreement but had important spatiotemporal differences. Comparison of geodetic mass balances with in-situ point and glacier-wide average mass balances had root mean square errors of 0.42 and 0.46 meters water equivalent. These results indicate that if emergence velocities and firn compaction are carefully considered, geodetic methods can provide accurate measurements of distributed mass balances over seasonal and annual time frames, yielding an improved understanding of glacier response and trend over these time scales. Such an understanding will facilitate improvements in model physics and parameterizations, thus improving projections for the magnitude and timing of future glacier losses and their effects on downstream communities and ecosystems.
Keywords: glaciology; mass balance; geodetic; remote sensing; ground penetrating radar